Solid electrolyte and method for producing same

A solid electrolyte with two crystalline phases, made from Li, P, S, and a halogen, addresses the conductivity issue in solid-state batteries, enhancing their performance.

JP7599550B2Active Publication Date: 2024-12-13MITSUI MINING & SMELTING CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023505510
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-11
Filing Date
2022-03-04
Publication Date
2024-12-13
Estimated Expiration
2042-03-04

AI Technical Summary

Technical Problem

Existing solid electrolytes do not achieve optimal ionic conductivity, limiting the performance of solid-state batteries.

Method used

A solid electrolyte composed of lithium (Li), phosphorus (P), sulfur (S), and a halogen (X) element, with two or more different crystalline phases, is produced by mixing raw materials and firing at specific temperatures to enhance ionic conductivity.

Benefits of technology

The resulting electrolyte exhibits significantly improved ionic conductivity, enabling higher performance in solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599550000004
    Figure 0007599550000004
  • Figure 0007599550000005
    Figure 0007599550000005
  • Figure 0007599550000006
    Figure 0007599550000006
Patent Text Reader

Abstract

This solid electrolyte includes a lithium (Li) element, a phosphorus (P) element, a sulfur (S) element, and an X element (where X represents at least one type of halogen element). Upon separation of peaks in a diffraction pattern in at least one of the range of 2θ=25.6±0.8°, the range of 30.2±0.8°, and the range of 31.6±0.8° in an X-ray diffraction pattern as measured by an X-ray diffractometer (XRD) using CuKα1 rays and CuKα2 rays, it is found that peaks P1 and P2 are present. Each of the peaks P1 and P2 originates from a different phase.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid electrolyte and a method for producing the same. [Background technology]

[0002] In recent years, solid electrolytes have been attracting attention as an alternative to the electrolytes used in many liquid batteries. Solid-state batteries using solid electrolytes are safer than liquid batteries that use flammable organic solvents, and are expected to be put to practical use as batteries with high energy density.

[0003] As a conventional technique related to solid electrolytes, for example, the technique described in Patent Document 1 is known. In recent years, research into such solid electrolytes has been actively conducted to obtain even better performance. For example, various studies have been conducted on solid electrolytes with high ionic conductivity. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] US2016 / 156064A1 [Patent Document 2] EP3026749A1 Summary of the Invention

[0005] An object of the present invention is to provide a solid electrolyte having superior ion conductivity.

[0006] The present invention relates to a compound semiconductor material comprising an element of lithium (Li), an element of phosphorus (P), an element of sulfur (S) and an element of X (X represents at least one halogen element), In an X-ray diffraction pattern measured by an X-ray diffractometer (XRD) using CuKα1 radiation and CuKα2 radiation, when a diffraction pattern in at least one of the ranges of 2θ=25.6±0.8°, 30.2±0.8°, and 31.6±0.8° is peak-separated, the diffraction pattern has a peak P1 and a peak P2, The peak P1 and the peak P2 are derived from different phases to provide a solid electrolyte.

[0007] The present invention also provides a process for producing a raw material composition comprising: mixing a lithium (Li) element source, a phosphorus (P) element source, a sulfur (S) element source, and a halogen (X) element source to obtain a raw material composition; and firing the raw material composition at a temperature higher than 500°C and lower than 700°C. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1(a) is a diagram showing an example of an X-ray diffraction pattern measured by an X-ray diffractometer for a conventional solid electrolyte consisting of a single phase, and FIG. 1(b) is a diagram in which the X-ray diffraction pattern shown in FIG. 1(a) is separated into two peaks. [Diagram 2] FIG. 2(a) is a diagram showing an example of an X-ray diffraction pattern measured by an X-ray diffractometer for the solid electrolyte of the present invention, and FIG. 2(b) is a diagram in which the X-ray diffraction pattern shown in FIG. 2(a) is separated into two peaks. [Diagram 3] FIG. 3 is a diagram showing the X-ray diffraction patterns of the solid electrolytes obtained in Example 2 and Comparative Example 2. [Figure 4] FIG. 4 is a diagram showing the X-ray diffraction patterns of the solid electrolytes obtained in Example 3 and Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described with reference to preferred embodiments thereof. The solid electrolyte of the present invention contains at least lithium (Li), phosphorus (P), sulfur (S) and halogen (X).

[0010] The X element contained in the solid electrolyte of the present invention is at least one halogen element, more specifically at least one element selected from chlorine (Cl), bromine (Br) and iodine (I). The X element may be one of these elements or a combination of two or more of them. From the viewpoint of enhancing the lithium ion conductivity of the solid electrolyte of the present invention, the solid electrolyte preferably contains at least Cl element as the X element. In particular, when only Cl element is contained as the X element, it is preferable because a solid electrolyte containing two or more different phases described below is easily obtained.

[0011] One of the features of the solid electrolyte of the present invention is that it contains two or more different phases. The two or more different phases are all crystalline phases. The inventor's study revealed that the solid electrolyte of the present invention exhibits ion conductivity superior to that of the conventional solid electrolyte due to the inclusion of two or more different phases. The reason for this is not completely clear, but the inventor believes that it may be due to the following reason. However, the scope of the present invention is not limited to such a theory. It is considered that the two or more different phases are all crystalline phases and exist in one crystal grain. The multiple crystal phases existing in one crystal grain all contain Li element, P element, S element and X element, but have different compositions. It is considered that the ion conductivity of the solid electrolyte as a whole is high due to at least one of the multiple crystal phases existing in one crystal grain being a high ion conductive phase. Alternatively, it is considered that the ion conductivity of the solid electrolyte as a whole is high due to the small interfacial resistance between the multiple crystal phases existing in one crystal grain.

[0012] The solid electrolyte of the present invention can be confirmed to contain two or more different phases based on an X-ray diffraction pattern measured by an X-ray diffractometer (XRD). In particular, the solid electrolyte can be confirmed to contain two or more different phases based on an X-ray diffraction pattern using X-rays of two different wavelengths as the XRD radiation source. As the X-ray source of two different wavelengths, it is convenient to use CuKα1 radiation and CuKα2 radiation. The CuKα1 radiation has a wavelength of 0.1540562 nm, and the CuKα2 radiation has a wavelength of 0.1544390 nm. The intensity ratio of the CuKα1 radiation to the CuKα2 radiation is theoretically about 2:1. Therefore, when the solid electrolyte to be measured by XRD is composed of a single phase, when the solid electrolyte is irradiated with the CuKα1 radiation and the CuKα2 radiation simultaneously, the obtained X-ray diffraction pattern is one in which the diffraction lines derived from the CuKα1 radiation and the diffraction lines derived from the CuKα2 radiation are superimposed with an intensity of 2:1, as shown in FIG. 1(a). When the overlapped diffraction pattern shown in Fig. 1(a) is mathematically separated by the least squares method, it is separated into peaks P1 and P2 having peak tops at the same position as shown in Fig. 1(b). In the present invention, the peak refers to a diffraction line derived from CuKα1 radiation and a diffraction line derived from CuKα2 radiation superimposed at an intensity ratio of 2:1.

[0013] As will be described in the examples below, the diffraction intensity data actually obtained by XRD is discrete (for example, the step width of the horizontal axis 2θ shown in FIG. 2(b) is 0.02°), so the peak top positions of the two peaks P1 and P2 mathematically separated by the least squares method described above will not be strictly the same, and there may be a slight shift in the peak top positions. In other words, theoretically, the peak top positions of the separated peaks are the same, but the peak top positions of the mathematically separated peaks may differ slightly. Therefore, in this specification, if the absolute value (Δ2θ) of the difference between the peak top positions of the two separated peaks P1 and P2 is 0.04° or less, the peak top positions of the two peaks are considered to be the same.

[0014] On the other hand, when the solid electrolyte of the present invention is irradiated with CuKα1 radiation and CuKα2 radiation simultaneously, the following occurs. For simplicity, the following description will be given of an example in which the solid electrolyte of the present invention contains two different crystal phases. In the case where the two different crystal phases are the A1 phase and the A2 phase, when the solid electrolyte of the present invention containing the A1 phase and the A2 phase is simultaneously irradiated with CuKα1 radiation and CuKα2 radiation, as shown in FIG. 2(a), the diffraction line P 11 and the diffraction line P originating from CuKα2 line 12 The intensity of the diffraction peaks is 2:1, and the A2 phase has a diffraction peak P originating from CuKα1 line. 21 and the diffraction line P originating from CuKα2 line 22 The intensity ratio of the four diffraction lines P 11 , P 12 , P 21 and P 22 A superimposed diffraction pattern is observed. When the diffraction pattern in which the diffraction lines shown in FIG. 2(a) are overlapped is mathematically separated into two peaks by the least squares method, the result is two peaks P1 and P2 having peak tops at different positions, as shown in FIG. 2(b). In this specification, peak P1 is the diffraction line P 11 and P 12 The peak P2 is a superposition of the diffraction line P 21 and P 22 In addition, when there are two peak tops, such as P1 in FIG. 2(b), the peak top is determined to be the one with the highest intensity.

[0015] As described above, when any diffraction pattern obtained by simultaneously irradiating a solid electrolyte with CuKα1 radiation and CuKα2 radiation is separated into two peaks, if the positions of the peak tops of the two peaks obtained by the separation are different, the solid electrolyte can be determined to contain two or more different crystal phases.

[0016] In the solid electrolyte of the present invention, in the X-ray diffraction pattern measured by XRD using CuKα1 radiation and CuKα2 radiation, when the diffraction pattern in at least one of the ranges of 2θ=25.6±0.8° (hereinafter, this range is also referred to as the “first range”), the range of 30.2±0.8° (hereinafter, this range is also referred to as the “second range”), and the range of 31.6±0.8° (hereinafter, this range is also referred to as the “third range”) is peak-separated, the peaks P1 and P2 are derived from different phases, which is preferable from the viewpoint of further increasing the ionic conductivity of the solid electrolyte. In particular, when the diffraction pattern in at least two angle ranges among the first range to the third range is peak-separated, the peaks P1 and P2 are derived from different phases, which is preferable from the viewpoint of further increasing the ionic conductivity of the solid electrolyte, and when the diffraction pattern in all of the first range to the third range is peak-separated, the peaks P1 and P2 are derived from different phases, which is even more preferable. In addition, in the solid electrolyte of the present invention, diffraction patterns may be observed at angles other than the above-mentioned ranges 1 to 3. Since the diffraction patterns observed in the ranges 1 to 3 are very strong when compared in terms of intensity, it was decided to perform peak separation on the diffraction patterns observed in these ranges.

[0017] As described above, the solid electrolyte of the present invention includes two or more different phases. The phases have different compositions and therefore different lattice constants. As a result, as described above, when the XRD diffraction pattern is separated into multiple peaks, multiple peaks with different peak top positions are obtained. When the two or more peaks derived from different phases are designated P1 and P2 in order from the low angle side, the angle difference Δ2θ (=2θ2-2θ1) between the angle 2θ1 at the peak top position of P1 and the angle 2θ2 at the peak top position of P2 is 0.04° or more, which is preferable because the ion conductivity of the solid electrolyte is further increased. From the viewpoint of making this advantage more prominent, the angle difference Δ2θ is more preferably 0.10° or more, and even more preferably 0.11° or more. On the other hand, the upper limit value of the angle difference Δ2θ is preferably 1.6° or less.

[0018] When the diffraction patterns of the first to third ranges are separated into two peaks P1 and P2, the intensity of peak P1 may be higher than the intensity of peak P2, or vice versa. From the viewpoint of further increasing the lithium ion conductivity of the solid electrolyte, the value of I1 / I2, which is the ratio of the intensity I1 of peak P1 to the intensity I2 of peak P2, is preferably 0.8 or less, more preferably 0.4 or less. The intensities I1 and I2 of peaks P1 and P2 referred to in this specification are parameters obtained when the diffraction pattern peaks are separated by the least squares method. In addition, when there are multiple peaks, it is preferable that the highest peak intensity among the multiple peaks has the above condition.

[0019] By the way, when XRD measurement is performed on a mixture of a solid electrolyte consisting of a first phase having a single composition and a solid electrolyte consisting of a second phase having a single composition, if a process for peak separation is performed on the diffraction pattern obtained by the measurement, multiple peaks with different peak top positions are obtained. However, this mixture does not have high lithium ion conductivity. The reason is that when a mixture is used, the interface resistance between the two phases cannot be reduced. In other words, the solid electrolyte of the present invention is made of a single substance (in other words, it is not a mixture) and has two or more different crystal phases. However, there is no obstacle to using the solid electrolyte of the present invention in a mixture with another solid electrolyte.

[0020] As described above, the solid electrolyte of the present invention contains Li, P, S and X elements. Examples of the solid electrolyte include, but are not limited to, Li2S-P2S5-LiX (X is at least one halogen element).

[0021] In particular, from the viewpoint of enhancing the lithium ion conductivity of the solid electrolyte, it is preferable that the solid electrolyte containing the above-mentioned elements contains a compound represented by the composition formula LiaPSbXc (X is at least one halogen element, a is a number equal to or greater than 3.0 and equal to or less than 6.0, b is a number equal to or greater than 3.5 and equal to or less than 4.8, and c is a number equal to or greater than 0.1 and equal to or less than 3.0).

[0022] In the above composition formula, a, which indicates the molar ratio of Li element, is preferably, for example, a number of 3.0 or more and 6.0 or less, more preferably a number of 3.2 or more and 5.8 or less, and even more preferably a number of 3.4 or more and 5.4 or less. Note that a may be less than 5.4. In the above composition formula, b, which indicates the molar ratio of the S element, is preferably, for example, a number from 3.5 to 4.8, more preferably from 3.8 to 4.6, and even more preferably from 4.0 to 4.4. Note that b may be less than 4.4. In the above composition formula, c is, for example, preferably a number of 0.1 or more and 3.0 or less, more preferably a number of 0.2 or more and 2.5 or less, and even more preferably a number of 0.4 or more and 2.0 or less. Compounds in which a, b, and c are within these ranges have sufficiently high lithium ion conductivity.

[0023] In particular, in the solid electrolyte of the present invention, it is preferable that the value of X / P, which is the molar ratio of the X element to the P element, is greater than 1.0 in order to further increase the lithium ion conductivity. From this viewpoint, the value of X / P is preferably 1.2 or more, and more preferably 1.6 or more. From the viewpoint of stably maintaining the argyrodite structure, it is preferable that X / P is 2.0 or less.

[0024] In the present invention, the compound obtained by feeding the amount of LiaPSbXc may contain elements other than Li, P, S, and X. For example, it may be possible to replace a part of the Li element with another alkali metal element, to replace a part of the P element with another pnictogen element, or to replace a part of the S element with another chalcogen element.

[0025] The solid electrolyte of the present invention preferably contains a crystal phase having an argyrodite crystal structure, because the lithium ion conductivity of the solid electrolyte can be increased. The argyrodite crystal structure is a crystal structure possessed by a group of compounds derived from a mineral represented by the chemical formula: Ag8GeS6. Whether or not the solid electrolyte of the present invention has a crystal phase having an argyrodite crystal structure can be confirmed by measurement using XRD. For example, in a diffraction pattern measured by XRD using CuKα1 radiation, the crystal phase having an argyrodite crystal structure shows characteristic diffraction peaks at 2θ=15.3°±1.0°, 17.7°±1.0°, 25.6°±1.0°, 30.2°±1.0°, 31.6°±1.0°, and 44.7°±1.0°. Depending on the elemental species constituting the solid electrolyte, in addition to the above diffraction peaks, characteristic diffraction peaks may be observed at 2θ=47.2°±1.0°, 51.7°±1.0°, 58.3°±1.0°, 60.7°±1.0°, 61.5°±1.0°, 70.4°±1.0°, and 72.6°±1.0°. For identification of the diffraction peaks derived from the argyrodite-type crystal structure, for example, the data of PDF No. 00-034-0688 can be used.

[0026] The solid electrolyte of the present invention has lithium ion conductivity in a solid state. The lithium ion conductivity of the solid electrolyte of the present invention is, for example, preferably 0.5 mS / cm or more, more preferably 1.0 mS / cm or more, particularly preferably 1.5 mS / cm or more, and particularly preferably 4.0 mS / cm or more at room temperature, i.e., 25° C. The lithium ion conductivity can be measured using the method described in the Examples below.

[0027] The solid electrolyte of the present invention can be preferably manufactured by the method described below. As the raw materials, a Li element source compound, a P element source compound, an S element source compound, and an X element source compound are used. As the Li element source compound, for example, lithium sulfide (Li2S) can be used. As the P element source compound, for example, diphosphorus pentasulfide (P2S5) can be used. As the S element source compound, when the Li element source compound and / or the P element source compound are sulfides, the sulfide can be used as the S element source compound. As the X element source compound, compound B (LiX) can be used. These raw materials are mixed so that the Li element, the P element, the S element, and the X element are in a predetermined molar ratio. Then, the mixed raw material composition is fired under an inert gas atmosphere, or fired under an atmosphere containing hydrogen sulfide gas. In particular, when the sintering temperature is within the temperature range described below, by using an inert gas atmosphere, such as a nitrogen atmosphere or an argon atmosphere, as the sintering atmosphere, it is possible to successfully obtain a solid electrolyte in which multiple crystal phases exist in one crystal grain.

[0028] In particular, in this manufacturing method, by adjusting the above-mentioned sintering conditions, it is possible to obtain a solid electrolyte in which multiple crystal phases exist in one crystal grain. Specifically, the inventors have found that multiple crystal phases are generated by sintering at a temperature higher than the sintering temperature that has been used so far, for example, the temperature used in Patent Document 1. From this viewpoint, it is preferable to set the sintering temperature to more than 500°C. On the other hand, if the sintering temperature is excessively high, a different phase that hinders lithium ion conductivity may be generated, so it is preferable to set the sintering temperature to less than 700°C. From the above viewpoint, it is more preferable to set the sintering temperature to 540°C or more and 660°C or less, and even more preferable to set it to 580°C or more and 620°C or less.

[0029] Regarding the firing time, provided that the firing temperature is within the above-mentioned range, it is preferably set to 1 hour or more and 7 hours or less, more preferably set to 2 hours or more and 6 hours or less, and even more preferably set to 3 hours or more and 5 hours or less.

[0030] The fired product thus obtained is subjected to a predetermined pulverization step. When the fired product is pulverized, either dry pulverization or wet pulverization may be performed, or both may be combined.

[0031] For dry grinding, for example, a jet mill, a ball mill, a rod mill, a vibrating ball mill, a planetary mill, a disk mill, etc. can be used. On the other hand, for wet grinding, various media mills can be used. Examples of media mills that can be used include a ball mill, a bead mill, a paint shaker, a homogenizer, etc.

[0032] When wet pulverization is performed, the solid electrolyte powder and the solvent are separated after the wet pulverization. To separate the two, for example, it is preferable to subject a slurry containing the solid electrolyte powder and the organic solvent to a solid-liquid separation treatment such as natural filtration, centrifugation, pressure filtration, or reduced pressure filtration. Alternatively, the slurry may be subjected to hot air drying or reduced pressure drying without performing these operations.

[0033] The solid electrolyte obtained by the above method can be used as a material constituting a solid electrolyte layer, a positive electrode layer, or a negative electrode layer. Specifically, the solid electrolyte of the present invention can be used in a battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer. That is, the solid electrolyte can be used in a so-called solid battery. More specifically, it can be used in a lithium solid battery. The lithium solid battery may be a primary battery or a secondary battery. There is no particular restriction on the shape of the battery, and for example, a laminate type, a cylindrical type, a square type, or the like can be adopted. The term "solid battery" includes a solid battery that does not contain any liquid or gel substance as an electrolyte, as well as an embodiment that contains, for example, 50 mass % or less, 30 mass % or less, or 10 mass % or less of a liquid or gel substance as an electrolyte.

[0034] When the solid electrolyte layer contains the solid electrolyte of the present invention, the solid electrolyte layer can be produced, for example, by dropping a slurry consisting of a solid electrolyte, a binder, and a solvent onto a substrate and scraping it off with a doctor blade, by contacting the substrate with the slurry and then cutting it with an air knife, by forming a coating film by screen printing or the like, and then removing the solvent by heating and drying, or by other methods. Alternatively, the solid electrolyte can be produced by forming a powdered solid electrolyte into a compact by pressing or the like, and then processing it appropriately. The thickness of the solid electrolyte layer is typically preferably 5 μm or more and 300 μm or less, and more preferably 10 μm or more and 100 μm or less, in terms of the balance between short circuit prevention and volumetric capacity density.

[0035] The solid electrolyte of the present invention is used together with an active material to form an electrode mixture. The ratio of the solid electrolyte in the electrode mixture is typically 10% by mass or more and 50% by mass or less. The electrode mixture may contain other materials such as a conductive assistant and a binder as necessary. An electrode layer such as a positive electrode layer and / or a negative electrode layer can be produced by mixing the electrode mixture with a solvent to prepare a paste, applying the paste to a current collector such as aluminum foil, and drying the paste.

[0036] As the positive electrode material constituting the positive electrode layer, a positive electrode material used as a positive electrode active material of a lithium ion battery can be appropriately used. For example, a positive electrode active material containing lithium, specifically, a spinel type lithium transition metal oxide and a lithium metal oxide having a layered structure, etc. can be mentioned. By using a high voltage positive electrode material as the positive electrode material, it is possible to improve the energy density. In addition to the positive electrode active material, the positive electrode material may contain a conductive material or other materials.

[0037] As the negative electrode material constituting the negative electrode layer, a negative electrode material used as a negative electrode active material in a lithium ion battery can be appropriately used. Since the solid electrolyte of the present invention is electrochemically stable, it can be used at a potential of lithium metal or a lower potential equivalent to that of lithium metal (about 0.1 V vs. Li +Carbonaceous materials such as graphite, artificial graphite, natural graphite, and non-graphitizable carbon (hard carbon), which are materials that are charged and discharged with a current of 0.1 wt. / Li, can be used as the negative electrode material. This can greatly improve the energy density of the solid-state battery. In addition, silicon or tin, which are promising high-capacity materials, can be used as the active material. In a battery using a general electrolyte, the electrolyte reacts with the active material during charging and discharging, causing corrosion on the active material surface, resulting in significant deterioration of the battery characteristics. In contrast to this, if the solid electrolyte of the present invention is used instead of the electrolyte and silicon or tin is used as the negative electrode active material, the above-mentioned corrosion reaction does not occur, and the durability of the battery can be improved. The negative electrode material may also contain a conductive material in addition to the negative electrode active material, or other materials. EXAMPLES

[0038] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to such examples. Unless otherwise specified, "%" means "% by mass".

[0039] Example 1 Li2S powder, P2S5 powder, and LiCl powder were weighed out to a total amount of 5 g so as to obtain the composition shown in Table 1 below. These powders were ground and mixed using a wet ball mill using heptane to obtain a mixed composition. The mixed composition was fired to obtain a fired product. The firing was performed using a tubular electric furnace. Nitrogen gas with a purity of 100% was circulated inside the electric furnace during firing. The firing temperature was set to 600°C, and firing was performed for 4 hours. The resulting fired product was crushed using a mortar and pestle, and then pulverized in a wet ball mill using heptane. The pulverized fired product was dried by vacuum drawing to remove the heptane. The dried fired product was sieved through a sieve with 1 mm openings to obtain the desired solid electrolyte powder. The obtained solid electrolyte was confirmed to have an argyrodite-type crystal structure.

[0040] [Examples 2 and 3 and Comparative Examples 1 to 3] A solid electrolyte powder was obtained in the same manner as in Example 1, except that the powders were mixed to obtain the composition shown in Table 1 and the firing conditions shown in the same table were adopted. The obtained solid electrolyte was confirmed to have an argyrodite-type crystal structure.

[0041] 〔evaluation〕 XRD measurements were performed under the following conditions for the solid electrolytes obtained in the Examples and Comparative Examples. Then, for each of the first to third ranges, the peaks were separated into two by the following method. The XRD patterns of the solid electrolytes obtained in Examples 2 and 3 and Comparative Examples 2 and 3 are shown in Figures 3 and 4. In addition, the lithium ion conductivity of the solid electrolytes obtained in the Examples and Comparative Examples was measured by the following method. The results are shown in Table 1 below.

[0042] [XRD measurement] The measurements were performed without exposure to air using a powder X-ray diffraction device "SmartLab SE" manufactured by Rigaku Corporation. The measurement conditions are as follows: Tube voltage: 40kV ·Tube current: 50mA X-rays: Cu Kα rays (CuKα1 rays and CuKα2 rays are included in the intensity ratio of 2:1) Optical system: focused beam method Detector: One-dimensional detector Measurement range: 2θ=10-120° Step width: 0.02° Scan speed: 1° / min

[0043] [Peak separation] The obtained XRD pattern (I XRD The diffraction pattern in the first to third ranges of the diffraction angle (represented as 2θ) was separated into two peaks P1, P2 and BG, which represents the background of the diffraction pattern. I XRD (2θ) = P1 + P2 + BG The peaks were separated by least squares curve fitting using the solver function of the software "Microsoft Excel for Office 365". Here, peaks P1 and P2 were expressed as a function of 2θ by the following formula.

[0044]

number

[0045] Furthermore, BG was expressed as a linear function in which a straight line connects two data points at both ends of each target range in the first to third ranges.

[0046] where I1 and I2 are positive constants that represent the intensities of peaks P1 and P2, respectively. 11 and P 12 respectively represent the diffraction lines originating from the CuKα1 radiation and the CuKα2 radiation that constitute the peak P1. Similarly, P 21 and P 22 represent the diffraction lines originating from the CuKα1 and CuKα2 rays that constitute the peak P2. In the curve fitting, the diffraction line P 11 and P 12 And P 21 and P 22 is expressed as follows using a pseudo-Voigt function, which is a weighted sum of a Lorentzian function and a Gaussian function with equal half-widths:

[0047]

number

[0048] Here, η 11 , η 12 , η 21 , η 22 are P 11 , P 12 , P 21 , P 22 is a constant between 0 and 1 that represents the proportion of Lorentzian components in Also, 2θ11 , 2θ 12 , 2θ 21 , 2θ 22 are P 11 , P 12 , P 21 , P 22 is a positive constant that represents the peak top position. Furthermore, w 11 , w 12 , w 21 , w 22 are P 11 , P 12 , P 21 , P 22 is a positive constant that represents the peak width of

[0049] In other words, the free parameters for deriving P1 and P2 by curve fitting are I1, η 11 , η 12 , θ 11 , θ 12 , w 11 , w 12 I2, η 21 , η 22 , θ 21 , θ 22 , w 21 , w 22 It is. However, from the viewpoint that the diffraction lines derived from CuKα1 and CuKα2 rays for the same phase must have the same shape, η 11 = η 12 , w 11 =w 12 , η 21 = η 22 , w 21 =w 22 A restriction was set. Also, η 11 , η 12 , η 21 , η 22 We set a constraint of 0 to 1.

[0050] Furthermore, since the difference in the positions of the diffraction lines originating from the CuKα1 line and the CuKα2 line in the first to third ranges is theoretically 0.06° to 0.08°, in order to simplify peak separation, 2θ 12 =2θ 11 +0.07, 2θ 22 =2θ 21 +0.07 Restrictions were also set. The index of validity for the least squares method was R<10. From the curve fitting, the angle difference Δ2θ between P1 and P2 is Δ2θ=2θ 21 -2θ 11 is obtained as:

[0051] [Lithium ion conductivity] The solid electrolytes obtained in the examples and comparative examples were heated at about 6 t / cm in a glove box purged with sufficiently dried Ar gas (dew point -60°C or lower). 2 A load of 10 ...

[0052] [Table 1]

[0053] As is clear from the results shown in Table 1, in the solid electrolyte obtained in each Example, when the diffraction pattern in the first range to the third range in the XRD diffraction pattern is peak-separated, it is found that two different peaks are observed. From this, it is found that two different phases are present in the solid electrolyte obtained in each Example. And, it is found that the solid electrolyte obtained in each Example, in which two different phases are present, has a higher lithium ion conductivity than the solid electrolyte of the comparative example. [Industrial Applicability]

[0054] According to the present invention, a solid electrolyte having higher ionic conductivity than ever before is provided.

Claims

1. Contains lithium (Li), phosphorus (P), sulfur (S) and X (X represents at least one halogen element); In an X-ray diffraction pattern measured by an X-ray diffractometer (XRD) using CuKα1 radiation and CuKα2 radiation, when the diffraction pattern in at least one of the ranges of 2θ=25.6±0.8°, 30.2±0.8°, and 31.6±0.8° is peak-separated, a peak P 1 and peak P 2 having The peak P 1 and the peak P 2 are solid electrolytes, each derived from a different phase.

2. In an X-ray diffraction pattern measured by an X-ray diffractometer (XRD) using CuKα1 radiation and CuKα2 radiation, when the diffraction patterns in the ranges of 2θ=25.6±0.8°, 30.2±0.8°, and 31.6±0.8° are peak-separated, the peak P 1 and the peak P 2 The solid electrolyte of claim 1 having

3. The solid electrolyte according to claim 1 or 2, wherein the X element includes at least chlorine (Cl).

4. 4. The solid electrolyte according to claim 1, wherein a molar ratio (X / P) of the X element to the phosphorus (P) element is greater than 1.

0.

5. The peak P 1 and the peak P 2 The solid electrolyte according to claim 1 , wherein the angle difference Δ2θ between the first and second electrodes is 0.04° or more.

6. 6. The solid electrolyte according to claim 1, comprising a crystalline phase having an argyrodite-type crystal structure.

7. A method for producing a solid electrolyte according to claim 1, comprising the steps of: A step of mixing a lithium (Li) element source, a phosphorus (P) element source, a sulfur (S) element source, and a halogen (X) element source to obtain a raw material composition; and calcining the raw material composition in an inert gas atmosphere at 540° C. or higher and 660° C. or lower for 2 hours or longer and 6 hours or shorter.

8. An electrode mixture comprising the solid electrolyte according to claim 1 and an active material.

9. A solid electrolyte layer comprising the solid electrolyte according to claim 1 .

10. A battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, the battery containing the solid electrolyte according to claim 1 .

Citation Information

Patent Citations

  • Sulfide-based solid electrolyte for lithium ion battery

    EP3026749A1

  • Sulfide-Based Solid Electrolyte for Lithium Ion Battery

    US20160156064A1

  • Method for producing sulfide solid electrolyte

    WO2020213340A1

  • Solid electrolyte and method for producing same

    WO2021054433A1